+0  
 
-2
288
2
avatar+2297 

Please explain

 Feb 20, 2018

Best Answer 

 #1
avatar+15375 
+2

First find the vertex.....can you tell me what that is?

 

 

 

 

 

 

 

From the graph the vertex is   h,k (or the x,y point) =  -3,4

 

 

Vertex form of parabola......we answered that in your las question....remember it?

 

 

 

 

 

y = a(x-h)^2 +k   is vertex form      Now let's put  -3 , 4 in there

 

y= a (x-(-3))^2 + 4       Now how can we find the value of 'a' ?  find a convenient point on the graph (not the vertex)     ....look at x = -5       at that point y = -4    Sub this in to the working equation then solve for 'a'

 

 

 

-4 = a (-5 +3)^2 +4        means 'a' = -2   soooooo the equation becomes

 

y = -2(x+3)^2 +4

 Feb 20, 2018
 #1
avatar+15375 
+2
Best Answer

First find the vertex.....can you tell me what that is?

 

 

 

 

 

 

 

From the graph the vertex is   h,k (or the x,y point) =  -3,4

 

 

Vertex form of parabola......we answered that in your las question....remember it?

 

 

 

 

 

y = a(x-h)^2 +k   is vertex form      Now let's put  -3 , 4 in there

 

y= a (x-(-3))^2 + 4       Now how can we find the value of 'a' ?  find a convenient point on the graph (not the vertex)     ....look at x = -5       at that point y = -4    Sub this in to the working equation then solve for 'a'

 

 

 

-4 = a (-5 +3)^2 +4        means 'a' = -2   soooooo the equation becomes

 

y = -2(x+3)^2 +4

ElectricPavlov Feb 20, 2018
 #2
avatar+2297 
+1

Tysm ^-^

RainbowPanda  Feb 20, 2018

23 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.